Prevention of postoperative scars in dark skin types using a fractional carbon dioxide laser: a clinical and histopathological split-scar study. Issue 2 (May 2017) - Darwish, Abdou M.; Abdel-Razek, Wael H.; Hassan, Khaled M.; Moftah, Noha H.; Abdel-Aziz, Mohamed F.
Abstract : Background: Treatment of mature postoperative scars is frustrating for both patients and doctors. Accordingly, a fractional carbon dioxide (CO2 ) laser could be used during the early postoperative period as a prophylaxis against scarring. However, its safety in patients with dark skin types and the histopathological changes during early treatment remain controversial. Objective: To evaluate the efficacy and safety of a fractional CO2 laser in the prevention of postoperative scars in patients with dark skin types, with assessment of its histopathological effect. Patients and methods: Six fractional CO2 laser sessions were performed at 2-week intervals on one part of early postoperative wounds of 20 patients in comparison with other untreated parts 3 months after the last session using the Vancouver scar scale (VSS). Using histopathological and computerized morphometric analysis, morphological changes in collagen and elastic fibers were assessed and a quantitative evaluation of epidermal thickness was performed 3 months after the last session. Results: In treated parts, there was a significant improvement in pliability, height, and total VSS score ( P ⩽0.05), with no significant difference in vascularity and pigmentation (>0.05), compared with untreated parts. Hypertrophic scars appeared in untreated parts of 40% of the patients. Histopathologically, collagen fibers were fine and well organized in treated parts (75%); however, they were arranged as fairly thickened hyaline bundles (75%), either disorganized (35%) or randomly, within nodules with some parallel fibers to the epidermis (40%) in untreated parts. Dense elastotic tissues, in untreated biopsies (80%), became less with the appearance of fine and well-organized fibers in treated biopsies (70%). There was a significant increase in the epidermal thickness of treated parts compared with untreated ones ( P <0.05). Conclusion: A fractional CO2 laser was effective, tolerable, and safe in the prevention of postoperative scars, especially the hypertrophic type, in patients with dark skin types. Histopathologically, remodeling of collagen and elastic fibers occurred with an increase in the epidermal thickness after its use.